Congenital Middle Mesocolic Hernia: A Rare Cause of Neonatal Intestinal Obstruction - Elias Chamely; Brice Antao (EL-Med-Pub, 2020)
Congenital mesocolic hernia is an extremely rare, but serious cause of intestinal obstruction in children. Given the rarity of this condition, delays in diagnosis and management can have catastrophic consequences. Congenital mesocolic hernias are usually caused by an abnormal rotation of primitive mid-gut and are divided into left and right congenital mesocolic hernias. We report and discuss the clinical and radiological features and management of a neonate with an extremely rare variant, congenital middle mesocolic hernia along with a literature review of this rare condition.